Cover Picture: [P3Se4]+: A Binary Phosphorus–Selenium Cation (Chem. Eur. J. 27/2015). Issue 27 (26th June 2015) - Feldmann, Kai‐Oliver; Wiegand, Thomas; Ren, Jinjun; Eckert, Hellmut; Breternitz, Joachim; Groh, Matthias F.; Müller, Ulrike; Ruck, Michael; Maryasin, Boris; Ochsenfeld, Christian; Schön, Oliver; Karaghiosoff, Konstantin; et al.
<x xml:space="preserve">Abstract</x> Joining forces pays off for T. Wiegand, H. Eckert, M. Ruck, C. Ochsenfeld, K. Karaghiosoff, J. J. Weigand et al., as described in their Full Paper on page 9697 ff. Although polyatomic cations of the p‐block elements of binary Group 15/Group 16 element cations are known, an example involving phosphorus has not been synthesized and characterized to date. Synthetic, spectroscopic, and computational insights are combined to uncover the novel nortricyclane‐type binary phosphorus–selenium cation [P3Se4]+, affording three distinct synthetic routes and detailed information on its structural, electronic, and dynamic properties.